PRISE EN CHARGE ANESTHÉSIQUE DES URGENCES OBSTÉTRICALES DANS LA VILLE DE LUBUMBASHI EN RD CONGO: ANESTHETIC MANAGEMENT OF OBSTETRIC EMERGENCIES IN THE CITY OF LUBUMBASHI IN DR CONGO - Zalambo, Sandra Sagboze; Dibue, Wilfrid Mbombo; Fefe, Rivain Iteke; Nsimire, Berthe Barhayiga; Kitungwa, Olivier Kasongo; Eddy, Wasso Milinganyo; Ildephonse, Teta wa Mwanza; Banza, Yves Mukalay; Muteya, Michel Manika; Isokomwa, Médard Bulabula (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Objective: To assess the problem of anesthetic management of obstetric emergencies in the city of Lubumbashi. Material and methods: This is a bi-centric cross-sectional documentary study with an analytical component carried out at the university clinics of Lubumbashi and at the Jason Sendwe hospital from October 1, 2020 to March 31, 2021. All women who underwent anesthesia for an obstetric emergency were included by studying the socio-demographic, clinical, obstetrical, anesthetic characteristics, the maternal-fetal outcome as well as their determinants. Data were entered with Excel and analyzed with SPSS 21.0. The ethical standards in force were scrupulously respected. Results: 160 were retained out of the 211 admitted (75.8%) with an average age of 29.7 ± 6.4 years. They were mostly married (92.5%), unemployed (87.5%), primiparous (60.6%) and ASA II (64.4%). These emergencies were relative at 51.2%, extreme at 25% and absolute at 23.8%. They had benefited from a caesarean section (96.9%). Locoregional anesthesia such as spinal anesthesia was the most practiced (75%) mainly with bupivacaine by junior doctors in anesthesia (96.2%). Extreme emergencies (25%) were mainly haemorrhagic. In multivariate analysis, maternal mortality (6.9%) was influenced by maternal age less than 18 years, delay in management, inadequate anesthetic management, pre-eclampsia and anemia, a consequence of haemorrhage. obstetrics. Neonatal deaths (10.6%) were associated with absolute and extreme urgency as well as high maternal blood pressure on admission. Conclusion: The anesthetic management of obstetrical emergencies still poses a serious problem in our environment with multifactorial morbidity and mortality, the reduction of which would require the improvement of the referral system, the equipment as well as the continuous training of anesthetic personnel and obstetrics